Hubungan Dukungan Keluarga Dan Kepatuhan Minum Obat Pasien Hipertensi - Elmiana Bongga Linggi; Kristia Novia; Yospina; Resny M.P Retraubun (Jurnal Keperawatan Florence Nightingale, 2026)
Hypertension is a non-communicable disease that represents a major global health problem and can lead to various serious complications, such as stroke, heart disease, and kidney failure. The purpose of this study was to determine the relationship between family support and medication adherence among hypertension patients. This research was conducted at the Sudiang Public Health Center (Puskesmas Sudiang) in Makassar. The method employed in this study was a quantitative approach with a cross-sectional study design. Sampling was conducted using a purposive sampling technique, yielding a total sample size of 109 respondents. The research instruments utilized were the Family Support Scale (FSS) and the Morisky Medication Adherence Scale (MMAS-8). Data analysis using the Chi-Square test yielded a $p\text{-value} = 0.001$ with a significance level of $α = 0.05$. This indicates that $p = 0.001 < α = 0.05$. Therefore, it can be concluded that there is a significant relationship between family support and medication adherence among hypertension patients at the Sudiang Public Health Center, Makassar. Controlling blood pressure through regular medication adherence in hypertension patients is essential to prevent complications caused by hypertension. Family support is highly required to improve compliance among hypertension sufferers.